2013
DOI: 10.3109/02713683.2013.841258
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Punctal Occlusion in Management of Dry Eyes after LaserIn SituKeratomileusis for Myopia

Abstract: Punctal plug insertion after LASIK surgeries may minimize the need for frequent lubricant application and hence improve patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Alfawaz et al [24] evaluated the effect of punctal plug use in preventing dry eyes after LASIK by comparing the results of the TBUT test, Schirmer’s test and OSDI in both eyes of the same patient treated with a lower punctal plug in one eye and using the other eye as control. They concluded that insertion of punctal plugs was significantly effective in improving dry eye symptoms and patient satisfaction after LASIK.…”
Section: Discussionmentioning
confidence: 99%
“…Alfawaz et al [24] evaluated the effect of punctal plug use in preventing dry eyes after LASIK by comparing the results of the TBUT test, Schirmer’s test and OSDI in both eyes of the same patient treated with a lower punctal plug in one eye and using the other eye as control. They concluded that insertion of punctal plugs was significantly effective in improving dry eye symptoms and patient satisfaction after LASIK.…”
Section: Discussionmentioning
confidence: 99%
“…While the pathophysiology of this complication is still evolving, a number of theories have been proposed to explain why dry eye occurs following refractive surgery, including exacerbation of preexisting dry eye disease [ 12 ], medicamentosa from postoperative medications [ 19 , 20 ], and damage to conjunctival goblet cells increasing tear hyperosmolarity and inflammation [ 19 , 21 23 ]. The interaction between the ocular surface and eyelids is an important factor in maintaining tear production and flow, which is also altered following surgery [ 10 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, 86% patients were free of symptoms of dry eye at 6-month follow-up and 76% of patients had stopped using lubricants after punctal occlusion with silicone punctal plugs [ 32 ]. Punctal occlusion is effective in treating many conditions that cause dry eyes such as Stevens-Johnson syndrome, keratoconjunctivitis sicca, contact lens wear, and superior limbic keratoconjunctivitis [ 33 ]. Another study evaluated canalicular occlusion with collagen and silicone plugs (Herrick plugs) in patients with dry eye related conjunctivitis.…”
Section: Methodsmentioning
confidence: 99%
“…Albietz et al reported that the use of lubricants and other options such as punctal plugs before refractive surgery increased the postprocedure goblet cell density [ 44 ]. A prospective randomized clinical trial evaluated punctal occlusion with punctal plugs after LASIK treatment for prevention of dry eye in 78 eyes of 39 patients [ 33 ]. Both eyes of the subjects underwent LASIK and lower punctal occlusion of one eye was performed while the other eye served as a control.…”
Section: Methodsmentioning
confidence: 99%